Conceptual Paper Proposing the ’Vishvas â€“ Valleti Consumer Empowerment Model’ - Vishvas, Radhika Jade; Valleti, Murugaiah (Indian Journal of Marketing, 2014)
The concept of ’consumer empowerment’ is widely seen as an area of interest not just to researchers, but also to retailers at large. As a result, it becomes important to explore the major retail factors that result in the experience of empowerment among consumers. The study tries to identify five major retail constructs, that is, retail store environment, expansion and control over choice, store convenience, store information, and consumer involvement based on vast and quality literature. Furthermore, after reviewing the existing five models of retail constructs, a new conceptual model the "Vishvas-Valleti Consumer Empowerment Model" is proposed. The proposed model tries to explain the combined effect of retail constructs resulting in the subjective experience of empowerment among consumers while shopping. Furthermore, the model signifies and emphasizes the importance of empowered consumers for businesses and the society in the long run.